A Subharmonic Super-Regenerative FMCW Radar With Improved Intermodulation Efficiency for Applications Beyond Cut-Off Frequency - Hahn, Leonhard; Vossiek, Martin; Carlowitz, Christian (IEEE Transactions on Microwave Theory and Techniques, 2023)
This article presents a novel subharmonic super-regenerative receiver (SHSRR) radar for high-sensitivity and low-noise operation in beyond- fmax frequency-modulated continuous wave (FMCW) applications. In contrast to conventional super-regenerative designs, the proposed concept is extended by an inherently implemented, subharmonic downconversion. This downconversion allows a tripling of both operation frequency and bandwidth and thereby enables the system’s operation beyond its gain limit. Operated with the novel SHSRR, the maximum operating frequency and bandwidth of FMCW transceivers is proven to be significantly increased. With local oscillator (LO) power requirements considerably reduced compared with passive mixer approaches, the concept is also suited for massive multichannel scaling. Optimized modulation signals are applied to the SHSRR concept, which intentionally boost the receiver’s nonlinearity and thus substantially improve previously achieved intermodulation efficiencies for the first time. The concept is verified experimentally with a 24-GHz FMCW radar transceiver implemented in planar microstrip technology. Due to the introduced optimization approach, extremely high sensitivity levels of well below −114 dBm have been accomplished, whereby the previously achieved noise figure is improved from almost 30 dB down to 11 dB. Power consumption was limited to 9 mW. This simple, novel concept is thus suitable for scaling to integrated circuits with a high number of receive channels at several 100-GHz carrier frequencies.<br
Keywords: Sensitivity; Receivers; Radio frequency; Oscillators; Modulation; Frequency modulation; Optimization